Fisheries of a minor reservoir, Shathamraj, Hyderabad - Piska, Ravi Shankar (Indian Journal of Fisheries, 2011)
The present study based on the data for 10 years deals with the role of a minorreservoir in fish production and the influence of stocking densities on fish production.Shathamraj, a minor reservoir with 25 ha of water spread is located inHyderabad. The reservoir is treated as stocking and capture system for developmentof the fisheries. The overall major carp production is 456.88kg/ha/yr, andthat of the rest being 56.25kg/ha/yr. The total fish production is 513.13kg/ha/yr.The major carp production increased significantly from 13.43 to 98.02%, and thatof others decreased drastically from 86.57 to 1.98%. The major carp seed (20 -40mm fry) alone was stocked in the reservoir with overall stocking rate of 5892fry/ ha/ yr. The major carp production considerably increased with stocking andthe maximum yield of carps was recorded at a stocking density of 8500 fry/ha/yr.It is concluded that Shathamraj is a highly productive reservoir in terms offishproduction.